Synthesis of a H-Sulfo-POSS catalyst and application in the acetalization of glycerol with 2-butanone to yield a biofuel additive. Issue 13 (28th May 2021) - Söderholm, Viktor; Esteban, Jesús; Vogt, Dieter
Abstract : This work shows the synthesis of a catalyst based on the functionalization of octaphenyl polyhedral oligomeric silsesquioxanes with sulfonic groups (H-Sulfo-POSS) and its performance in the acetalization of glycerol to yield a biobased fuel additive. Abstract : Nanosized polyhedral oligomeric silsesquioxanes (POSS) have been employed as molecular weight enlarged structures for different purposes owing to their ease of synthesis and modification. In this work, the commercially available compound octaphenyl-POSS has been modified with chlorosulfonic acid to obtain multifunctional acidic materials (H-Sulfo-POSS) with different degrees of functionality in the structure. The synthesized materials have been characterized by ion exchange capacity, degree of sulfonation, 1 H-NMR, ATR-IR spectroscopy and SEM. These H-Sulfo-POSS nanocomposites were then applied to the acetalization of glycerol with 2-butanone to yield the corresponding ketal, which is a product of interest as an oxygenate fuel additive. The catalytic activity in dynamic experiments of the H-Sulfo-POSS (2601 h −1 ) material with the highest degree of sulfonation was even higher than that shown by the molecular catalyst para -toluene sulfonic acid (PTSA) (2256 h −1 ) and better than Amberlyst 36 (213 h −1 ); however, upon recycling by centrifugation of the catalyst, the activity of this material was not very stable. On the other hand, the material with the lowest degree of sulfonation showed not only higher activity than Amberlyst 36, but also very stable activity after reutilization throughout 10 runs.